Monitoring feet temperature using thermography - Bento, David (2014)
Studies show that regular monitoring of feet temperature may limit the incidence of disabling conditions such as foot ulcers and lower-limb amputations. Infrared thermometry and liquid crystal thermography were identified as the leading technologies in use today. In this study, we analysed the maximum temperature and tested some mathematical models for the foot temperature distribution.